(NgRAMATI^NO(B-(NSTIL)QÆSTI^NIJ SLOWNIK [EW^ENKOWOÇ MOWI (B=s)E Grammaticat and stylistic lexicon of shevchenko's poetri - )Qæ(NLARÆONs)E (NMITROPOLIT )QæLARÆON(B,s)E 1882 - 1972; )Qæ(NNSTITUT DOSLÆDÆW wOLINÆs)E ((Nw)QÆNNÆPEG (B:s)E (NtOWARISTWO (B"(NwOLINX(B",s, 1961)
(NrOZGLQNUT)QÆ MOWNO(B-(NSTILÆSTI^NÆ OSOBLIWOSTÆ POEZÆJ t(B. (Ng(B. (N{EW^ENKA(B. (NsLOWNIK PODAÃ [IROKIJ MATERÆAL DLQ WIW^ENNQ {EW^ENKOWOÇ MOWI NA[IMI SU^ASNIKAMI(B.s)E
(NdOD(B. (NTIT(B. (NARK(B. (NANGL(B.s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NuKRA)QÇNSXKA MOWAs)E -- (NgRAMATIKAs; (NSLOWNIKIs; (NR)QÆDKÆSNE WIDANNQs)E